Home-region orientation in international expansion strategies - Banalieva, Elitsa R; Dhanaraj, Charles (Journal of International Business Studies, 2013)
Despite the emerging consensus that most multinational enterprises (MNEs) are regional, systematic theory explaining regionalization is conspicuously absent, and empirical findings on its implications for MNE performance remain mixed. Drawing on internalization theory, we suggest that technological advantage and institutional diversity determine firms’ home-region orientation (HRO), and we posit a simultaneous relationship between HRO and performance. We apply insights from the firm heterogeneity literature of international trade to explain the influence of technology on HRO. We predict a negative and nonlinear impact of technological advantage on HRO driven by increasing returns logic, and a negative impact of institutional diversity on HRO driven by search and deliberation costs. We find empirical support for our model using simultaneous equations methodology on longitudinal data on Triad-based MNEs. Performance significantly reduces HRO, but HRO does not have a significant effect on performance.